Sistem Pendukung Keputusan Pemilihan Best Employee Dengan Menerapkan Metode MABAC - Barus, Ernita Br (TIN: Terapan Informatika Nusantara, 2022)
This study aims to identify and evaluate the existing assessment system/procedure and to produce a decision support system for selecting the best employee based on employee performance at PT Smart Glove Indonesia. The selection of the best employees at this time is based on the leadership's personal assessment with reference to the criteria of knowledge, responsibility, cooperation, discipline, and employee attendance which results in irrelevant decisions due to lack of control from the leadership. This system was developed using the multi-attributive border approximation area comparison (MABAC) method using MySQL programming and Microsoft Visual Basic Net 2008. This information system can be used to process employee data in the employee evaluation process and selecting the best employees. The output of this system is the calculation value of the best employee selection at PT Smart Glove Indonesia using the multi-attributive border approximation area comparison (MABAC) method and the best employee recommendation for PT Smart Glove Indonesia